2004
DOI: 10.1111/j.1440-1746.2003.03318.x
|View full text |Cite
|
Sign up to set email alerts
|

Double point mutation in the core promoter region of hepatitis B virus (HBV) genotype C may be related to liver deterioration in patients with chronic HBV infection

Abstract: Genotype C might be one of the worse prognostic markers in patients with chronic HBV infection, possibly because of mutation in the CP region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
3
8
1
Order By: Relevance
“…This is probably because of the limited number of patients with genotype B infection in this study. Consistent with the previous reports on the literature [52][53][54][55], genotype C showed a much higher frequency of BCP mutation than genotype B. T1762/A1764 mutation occurred in 92.4% of genotype C and 37.5% of genotype B (P < 0.01). T1766 and A1768 were exclusively found in patients infected with genotype C. These data supported the hypothesis that the association between HBV genotype C and HCC was probably not genuine but was due to the high percentage of BCP mutation in patients with HBV genotype C infection [56].…”
Section: Discussionsupporting
confidence: 94%
“…This is probably because of the limited number of patients with genotype B infection in this study. Consistent with the previous reports on the literature [52][53][54][55], genotype C showed a much higher frequency of BCP mutation than genotype B. T1762/A1764 mutation occurred in 92.4% of genotype C and 37.5% of genotype B (P < 0.01). T1766 and A1768 were exclusively found in patients infected with genotype C. These data supported the hypothesis that the association between HBV genotype C and HCC was probably not genuine but was due to the high percentage of BCP mutation in patients with HBV genotype C infection [56].…”
Section: Discussionsupporting
confidence: 94%
“…The rate of HBe seroconversion following entecavir treatment for 3 years in this study (26%), is somewhat lower than previously reported for patients treated with adefovir or lamivudine for 3 years (40% and 43%, respectively) [24,33]. This may be related to the large proportion (92%) of HBV genotype C patients enrolled in this study, which has previously been associated with delayed HBe seroconversion [10,34].…”
Section: Number Of Patientscontrasting
confidence: 78%
“…The vast majority of CHB patients in Japan are infected with hepatitis B virus (HBV) of genotype C [6,7]. Infection with genotype C virus has been associated with delayed HBe seroconversion, more advanced liver disease, and increased probability of HCC development [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…One prospective study has shown that patients with HBV genotype C infections are more likely to develop HCC 29 . The 1762 T /1764 A mutations have been reported to be more common in chronic HBV genotype C infections (76%) than in genotype B infections (7%) 30 . However, confirmation has not been reported nor have completely prospective studies been reported evaluating the risk associated with these two mutations.…”
Section: Cirrhosis As a Contributing Factor To Hccmentioning
confidence: 99%